1988
DOI: 10.1111/j.1476-5381.1988.tb16542.x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium‐dependent inhibition by PN200‐110 enantiomers of nicotinic adrenal catecholamine release

Abstract: 1 Dimethylphenylpiperazinium (DMPP) or high K concentrations evoke catecholamine release from perfused cat adrenal glands; in both cases the secretory response was significantly enhanced in the absence of Na. Tetrodotoxin did not modify the nicotinic secretory response. 2 The (+)-and (-)enantiomers of the dihydropyridine Ca channel blocker PN200-110 show a high degree of stereoselectivity in the inhibition of catecholamine secretion evoked by high K or by DMPP in the presence of Na, the (+)-enantiomer being 57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…Hof et al [4] showed a large difference in pharmacological effects of enantiomers, where (1)-(S)-IRD presented inhibition of depolarization-induced contraction of rabbit aorta in vitro 160 times greater than (À)-(R)-IRD, and with in vivo studies, this difference was found 30-and 300-fold, with respect to subendocardial coronary blood flow and blood pressure, respectively. Other differences in activity have been reported [5,6]. Since the pharmacological effects of the enantiomers can be different, there is a need for the development of enantioselective methods.…”
Section: Introductionmentioning
confidence: 96%
“…Hof et al [4] showed a large difference in pharmacological effects of enantiomers, where (1)-(S)-IRD presented inhibition of depolarization-induced contraction of rabbit aorta in vitro 160 times greater than (À)-(R)-IRD, and with in vivo studies, this difference was found 30-and 300-fold, with respect to subendocardial coronary blood flow and blood pressure, respectively. Other differences in activity have been reported [5,6]. Since the pharmacological effects of the enantiomers can be different, there is a need for the development of enantioselective methods.…”
Section: Introductionmentioning
confidence: 96%
“…Uma vez que os efeitos farmacológicos dos enantiômeros da IRD podem ser diferentes (CARDENAS et al, 1988;HANDROCK et al, 1999), há uma necessidade do desenvolvimento de métodos enantiosseletivos. Diversos métodos, utilizando a cromatografia quiral, tem sido apresentados para a análise enantiosseletiva da IRD.…”
Section: Aplicação Do Método Em Formulação Farmacêutica De Ifn α-2aunclassified